Pengaruh Lama Perebusan Terhadap Kandungan Kafein Kopi Arabika (Coffea arabica L.) Kintamani - Jaya Kusuma, Karmando; Sugitha, I Made; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i01.p02, 2024)
Decaf coffee is coffee with a very low caffeine content and is different from normal coffee in general, the caffeine content is around 0.1% -0.3%. Decaffeination is the process of reducing the caffeine content in rice coffee prior to the roasting process. This study aims to determine the effect of boiling time on the caffeine content of Kintamani Arabica coffee and to determine the proper boiling time to obtain the lo w-caffeine Arabica Kintamani coffee . This study used a complet e ly randomized desig n with bo iling duration consisting of 5 levels, namely: 0 minutes, 30 minutes, 60 minutes, 90 minutes and 120 minutes and was repeated 3 times to obtain 15 experimental units . Parameters observed were moisture content, ash content, pH, caffeine content, sensory including bitter taste, sour taste, aroma, taste, color and overall acceptance. The data obtained were analyzed using variance and continued with Duncan's Multipl e Rang e Test. Based on the results of the analysis, the boiling trea t ment of Kintamani a rabica co ffee beans had a significant effect on the moisture content, ash content, pH value, caffeine content and sensory value of the coffee. The best boiling time for Kinta mani Arabica g re e n bean is 90 minut es with the characteristics of ground coffee produced by a water content of 1.95%, ash content of 3.02%, pH of 5.57 and caffeine content of 1.66%, color, aroma, taste, overall reception favored with a bitter and sou r tast e . Keyword: K intamani arabica c offe e, boiling time, caffeine